IFPRI Malawi monthly maize market report, February 2025 - International Food Policy Research Institute; Banda, Chimwemwe (International Food Policy Research Institute, 2025)
Highlights  Retail prices of maize increased by 32 percent in February as a result of a similar decrease in the value of Malawi Kwacha on the informal market.  Maize prices were lowest in the Northern region, where informal imports from Tanzania enter the country, and increased southward.  At the market exchange rate, retail prices of maize in Malawi were similar to those in Zambia and Mozambique, but lower than in Zimbabwe.